Experiencia profesional adquirida en el área operacional-control de calidad de la empresa prestadora de servicios, Seda Huánuco S.A. Unidad Operativa Aucayacu - Cárdenas Larrea, Marcos Roberto (2024)
In this we present the contributions given or implement in the company EPS Seda Huánuco S.A. – Aucayacu Operational Unit, in the Operational Area – Quality Control which is divided in two sub areas: Operational and quality control – the main functions performed are: The preparation of documents, the monitoring and laboratory analysis necessary to efficiently and reliably obtain results obtained with precision of the analyzed samples. This allowed us to draw some conclusions about the quality of the product, a better control of the management of the results and serves as a basis for operational actions; for this reason it is necessary to subject the natural water (surface and underground) to various operations and processes that carry it to be considered drinking water. The methodology in the water purification process carried out in the water purification plants, according to the quality regulations in the different countries and specifically in the Peruvians regulations, which are under the direct responsibility of the chemical engineer, whose professional training allows you to function efficiently in the process of making water drinkable, providing quality conditions for the human consumption. This technical report of professional experience corresponds to the bachelor MARCOS ROBERTO CARDENAS LARREA. Experience acquired at the EPS Seda Huánuco S.A. – Aucayacu Operational Unit in its Operational Area – Quality Control and has also and has also allowed it to function in administrative management and resource management.